An analysis of the effectiveness of funding systems of State Universities in Zimbabwe period 2010 to 2014 - Nyawo, Samson (Midlands State University, 2017)
Inadequate state subsidy, and purely monetary interpretation of the private social rates of return from state Universities combined with the view that not all beneficiaries of public subsidies are students from poor background has led to a situation where there is a demand that the beneficiaries, that is parents and students be made to share the cost of providing University education. Furthermore, the need for cost effectiveness and supplementary income to argument public subsidy also pushed universities to devise cost sharing, cost cutting and revenue generation schemes. The measures taken ranged from the introduction of tuition and other fees and admission of privately sponsored students (parallel programs and block release basis), including foreign students in some cases, commercialisation of service units and university assets (engineering equipment) and introduction of demand driven courses. The study sets to find out the effectiveness of the funding systems in place and to recommend others. The descriptive survey approach was used. Questionnaires targeting the seven state Universities were sent from which middle and senior managers were used. Findings indicate that funding systems in state universities were not effective as such various social evil have cropped up such as high student debt, increased rate of prostitution, crowded online services, high staff turnover, lack of research culture and low pay resulting in half baked graduates. Recommendations to adopt other methods tried in the region were done.